2022
DOI: 10.22201/igeof.00167169p.2022.61.1.2126
|View full text |Cite
|
Sign up to set email alerts
|

Mineral lithotype identification on the andrill AND-2A drillcore, antarctica by using ternary mineral rock physics templates built from a self-consistent approach

Abstract: In this work, wet bulk density ?WBD and compressional wave velocity VP core log data obtained along the AND-2A drillcore are plotted on density-velocity ternary mineral Rock Physics Templates (RPTs) built from a Self-Consistent (SC) micromechanics modelling with the purpose to deter- mine data trends that allow us to assist in identifying mineral lithotypes and lithological features throughout the 1138 m length of the drillcore. The elastic properties of the three dominant miner- als present in the drillcore (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
2
4
0
Order By: Relevance
“…Conversely, our interpretation of Gardner's relationship is supported by the distribution of mineral lithotypes shown by the RPTs over the AND-2A drillcore. Additionally, these findings are in line with the primary lithological characteristics listed by Fielding et al [8]. Also, exist a direct relationship between the lithological features of the six chosen samples and the predicted mineral lithotypes.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Conversely, our interpretation of Gardner's relationship is supported by the distribution of mineral lithotypes shown by the RPTs over the AND-2A drillcore. Additionally, these findings are in line with the primary lithological characteristics listed by Fielding et al [8]. Also, exist a direct relationship between the lithological features of the six chosen samples and the predicted mineral lithotypes.…”
Section: Discussionsupporting
confidence: 90%
“…The qualitative X-ray diffraction (XRD) study (see Table 4) performed on these samples reveals that the feldspars, mica, carbonates, calcium minerals, clay minerals, and carbonates are their primary constituent minerals. We can see from Tables 2 and 3 that the six chosen samples and the described lithology in Fielding et al [8] are in agreement with the lithology identified by the Gardner and SC approaches. As a result, LSU 2, LSU 3, and LSU 4 are all composed primarily of siliceous rocks rich in clay.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations